Improving Higher Education Resource Allocation Efficiency and Its Spatial Correlation for Sustainable Development in China - Weidong Guo (Decision Making: Applications in Management and Engineering, 2024)
Amidst global economic integration and the expansion of the knowledge economy, higher education serves as a fundamental pillar of national innovation systems. The strategic importance of its resource allocation efficiency is critical for attaining sustainable development objectives. This study introduces an advanced three-stage super-efficient slacks-based measure (SBM)-data envelopment analysis (DEA) model, incorporating spatial econometric analysis to conduct a multi-dimensional assessment of higher education resource allocation efficiency (HERAE) across 31 Chinese provinces from 2015 to 2022. Unlike the conventional DEA model, this approach innovatively integrates the advantages of the super-efficient SBM model in addressing non-radial relaxation with the Three-stage DEA model’s capability to account for environmental variables. It effectively mitigates the shortcomings of prior research that disregards environmental influences and stochastic disturbances. Empirical findings reveal that, after adjusting for environmental variables, the average technical efficiency (TE) and scale efficiency (SE) of higher education resource allocation (HERA) in China declined to 0.553 and 0.659, respectively, whereas pure technical efficiency (PTE) increased to 0.857. This indicates that traditional evaluation techniques tend to overestimate efficiency levels. The overall efficiency in the eastern region (0.739) was significantly greater than in the central (0.689), north-eastern (0.486), and western (0.368) regions. Three principal factors influencing efficiency include the level of regional economic development, governmental support for education, and the extent of social development. Spatial analysis revealed that the global Moran index fluctuated between 0.160 and 0.414 from 2015 to 2021, yet in 2022, it shifted to a non-significant negative correlation due to the pandemic’s impact. Consequently, this study suggests policy measures such as establishing a regional coordination framework, strengthening digital governance, and fostering collaboration among educational institutions to support decision-making